VD_FINDINFO AI 288/09 - 336/09 vom 28. Oktober 2009 - VD Tribunal cantonal (2009)
RADIATION DU RÔLE, SUSPENSION DE LA PROCÉDURE | 43 al. 1 LPGA, 56 al. 2 LPGA, 61 let. a LPGA, 25 LPA-VD, 49 al. 1 LPA-VD, 94 al. 1 let. c LPA-VD